An exploratory qualitative assessment of self-reported treatment outcomes and satisfaction among patients accessing an innovative voluntary drug treatment centre in Malaysia. - Ghani, Mansur A; Brown, Shan-Estelle; Khan, Farrah; Wickersham, Jeffrey A; Lim, Sin How; Dhaliwal, Sangeeth K; Kamarulzaman, Adeeba; Altice, Frederick L (The International journal on drug policy, 2015)
In Malaysia, compulsory drug detention centres (CDDCs) hold suspected drug users for two years without adjudication. Acute detoxification without healthcare access has been documented. CDDCs are criticized globally due to ineffectiveness in treating addiction and human rights violations. In response, the Malaysian government began transitioning these facilities into voluntary drug treatment centres known as "Cure and Care" (C&C) centres that embrace a holistic treatment-based approach to drug addiction rehabilitation.